Why she plays : the world of women's basketball - Baker, Christine A. (University of Nebraska Press, 2008)
Baker sets the stage with a quick look at current statistics and trends in women's basketball nationwide, noting the profound changes in the last thirty-five years. A series of exclusive interviews then takes us into the heart and soul of the sport. Her subjects are players and coaches, from neophytes to stars such as Dawn Staley and Nancy Lieberman; from legendary coaches such as Jody Conradt to the masterminds of USA Basketball and the 1996 Women's Dream Team; from Donna Lopiano, former CEO of the Women's Sports Foundation, to tomorrow's Olympic athletes. A richly detailed, all-encompassing portrait of the sport, these interviews offer a wealth of insight into the game, American sports culture, and, indeed, why Baker plays.